Hubungan Tingkat Pengetahuan Tentang Kanker Serviks Dengan Sikap Terhadap Pemeriksaan Pap Smear Pada Wanita Usia Subur di Dusun Pancuran Bantul Tahun 2017 - Amalia Ratna Kusumaningrum; Siti Tyastuti; Hesty Widyasih (POLTEKKES KEMENKES YOGYAKARTA, 2017)
In Indonesia, the highest prevalence of cervical cancer is located in D.I Yogyakarta. Low knowledge of cervical cancerbecomes one of the factors causing high incidence of cervical cancer. Cervical cancer can be prevented by using Pap smearearly on. Coverage of Pap smear can be used below 10%. Good knowledge also can support Pap smear. The purpose of thisstudy is to know the correlation between knowledge level on cervical cancer and attitude toward Pap smear on women atfertile age in Pancuran, Bantul, 2017. The population was 191 women's fertile age at Pancuran village, Bantul. This studyused cross sectional study design with simple random sampling technique. The sample of this study was 90 participants. Thedata collection used the questionnaire on the level of knowledge and the attitude on April 16, 23, and 27, 2017. Data analysisused Chi-Square test. The result of the study shows 80% of the sample was elementary, economic status was 69% belowBantul minimum wage, 82% had not done Pap smear test before, 48% with good knowledge, and 39% the attitude wassupporting Pap smear. The result of statistical test showed p-value 0.000, with the power was moderate (0.504). This studyconcludes that there is a correlation between the level of knowledge and the attitude toward Pap smear test which the value ismoderate.